American film cycles : reframing genres, screening social problems, & defining subcultures - Klein, Amanda Ann, 1976- (Film and media studies, 2011)
A series of movies that share images, characters, settings, plots, or themes, film cycles have been an industrial strategy since the beginning of cinema. While some have viewed them as "subgenres," mini-genres, or nascent film genres, Amanda Ann Klein argues that film cycles are an entity in their own right and a subject worthy of their own study. She posits that film cycles retain the marks of their historical, economic, and generic contexts and therefore can reveal much about the state of contemporary politics, prevalent social ideologies, aesthetic trends, popular desires, and anxieties. American Film Cycles presents a series of case studies of successful film cycles, including the melodramatic gangster films of the 1920s, the 1930s Dead End Kids cycle, the 1950s juvenile delinquent teenpic cycle, and the 1990s ghetto action cycle. Klein situates these films in several historical trajectories--the Progressive movement of the 1910s and 1920s, the beginnings of America's involvement in World War II, the "birth" of the teenager in the 1950s, and the drug and gangbanger crises of the early 1990s. She shows how filmmakers, audiences, film reviewers, advertisements, and cultural discourses interact with and have an impact on the film texts. Her findings illustrate the utility of the film cycle in broadening our understanding of established film genres, articulating and building upon beliefs about contemporary social problems, shaping and disseminating deviant subcultures, and exploiting and reflecting upon racial and political upheaval.